A COMPARISON OF OPEN VERSUS CLOSED SUPRACONDYLAR FRACTURE HUMERUS FIXATION IN PAEDIATRIC POPULATION IN TERMS OF POST-OPERATIVE STIFFNESS AND RANGE OF MOTION (The Research of Medical Science Review, 2025)
Background: Supracondylar humerus fractures are among the most common pediatric fractures, often resulting from falls or sports injuries. The management of these fractures typically involves either closed or open reduction, with varying outcomes. Despite extensive research, the optimal approach remains unclear. This study aims to compare the efficacy of closed versus open reduction in terms of post-operative stiffness and range of motion in the pediatric population. Objectives: To compare the functional outcomes of closed versus open reduction for pediatric supracondylar humerus fractures, focusing on post-operative stiffness and range of motion, and to determine the best approach for these fractures. Study Design & Setting: This study was conducted at Rawalpindi Teaching Hospital, Rawalpindi from 1st September 2024 to 28th February 2025. Methodology: The study included pediatric patients aged 2-14 years diagnosed with unilateral supracondylar humerus fractures. A total of 180 patients (90 in each group) were randomly assigned to either closed reduction with K-wiring or open reduction with K-wiring under general anesthesia. Preoperative range of motion, operative time, and intraoperative blood loss were recorded. Post-operative efficacy was assessed at 6, 12, and 24 weeks using Flynn’s criteria, focusing on excellent and good outcomes. Data were analyzed using SPSS 26.0, with a significance level of p ≤ 0.05. Results: The mean operative time was 48.2 ± 10.3 minutes in the closed reduction group and 68.5 ± 12.7 minutes in the open reduction group, with no significant difference (p=0.65). The mean blood loss was 75.6 ± 20.4 ml in the closed reduction group and 120.3 ± 25.7 ml in the open reduction group, with no significant difference (p=0.45). The mean preoperative range of motion was 120.5° (±12.4) in the closed reduction group and 119.7° (±13.1) in the open reduction group, with no significant difference (p=0.54). Functional outcomes, as assessed by Flynn’s criteria, were comparable, with 55.6% of closed reduction patients and 46.7% of open reduction patients achieving excellent outcomes (p=0.26). The overall efficacy, defined as excellent or good outcomes, was 88.9% in the closed reduction group and 85.6% in the open reduction group (p=0.52). Conclusion: Closed and open reduction techniques resulted in comparable outcomes in pediatric supracondylar humerus fractures, suggesting that either approach can be effective depending on fracture complexity and surgeon experience.